Construction and validation of a systematization instrument for nursing in intensive care - Daniela Silva de Araújo; Andreza Freire de França; João Kelvin da Silva Mendonça; Ana Rita de Cássia Bettencourt; Thatiana Lameira Maciel Amaral; Patricia Rezende do Prado (Rev Rene)
Objective: construction and validation of a systematization instrument for Nursing Care, characterizing the profile of patients of an intensive care unit in the north of Brazil. Methods: it was a descriptive methodological study that followed a nursing process model in five phases. Results: it was suggested that the instrument be constructed in two formats; one for admission and another for daily assessment. Some items were removed from the instrument according to content validation content by the nurses. Of the 45 patients evaluated, 60.0% were men, 44.0% were married, 40.0% had low education levels, chronic renal failure and cancer. The main nursing diagnoses were risk for infection (100.0%) and impaired physical mobility (97.8%). The main nursing interventions were: handwashing, changing intravenous access, performing aseptic techniques and moving patients every 2 hours. Conclusion: construction and content validation were carried out successfully, promoting instruments capable of providing quality nursing care for patients in intensive care.